Professional Values in Guiding Professional Behavior of Nurses: A Phenomenological Study - Rutmauli Hutagaol; Devis Enjelia; Ira Kusumawati (Alta Dharma Publisher, 2021)
Introduction: Nurses must have knowledge and awareness concerning professional values as standards to provide safe and high-quality care. Objective: The study aimed to explore the professional’s value in directing nurses’ behavior. Method: A qualitative study design with a phenomenology approach was applied in this study. We involved ten nurses with ten years of working experience and acting as role models in nurse managers. The data analysis used the Colaizzi method. We found the professional nursing values among nurses, including human dignity, integrity, professional practice, altruism, and compassion. Dimensions that underlying the professional values are knowledge, skill, and attitude. Results: The following four themes reflected how to apply nurses value: 1) Competence in facing challenges; 2 Nurses provided services based on knowledge and skills, a sense of help and compassion for love as a form of worship and commitment to the profession; 3) feeling satisfied in undergoing the nurse profession; 4) expectations of professional development. Professional nurses have a positive attitude and a hope for professional development. Conclusion: The hospital could improve nursing education and research by providing evidence-based practices for self-development. Recommendation: Nurse managers also can provide services based on science, skills, and attitudes as a form of worship and commitment to the profession, becoming a role model for the nurse-led